Comparative efficiency of extraction techniques for bioactive compounds in Cinnamomum zeylanicum - Culas MS; Kaur L; Popovich DG; Rashidinejad A (Elsevier Ltd, 2025)
Cinnamomum zeylanicum is a plant well-known for its antioxidant-rich bioactives. This study assessed its total phenolic (TPC) and flavonoid contents (TFC), antioxidant activity, and key bioactives (cinnamaldehyde, eugenol, and cinnamic acid) using two extraction methods: accelerated solvent extraction (ASE) and ultrasonic-assisted extraction (UAE), with solvents including ethanol, methanol, acetone, and water. ASE with 50 % ethanol yielded the highest TPC (6.83 ± 0.31 mg GAE/g), TFC (0.50 ± 0.01 mg QE/g), cinnamaldehyde (19.33 ± 0.002 mg/g), eugenol (10.57 ± 0.03 mg/g), and cinnamic acid (0.18 ± 0.004 mg/g), making it superior to UAE. However, UAE with 50 % ethanol showed the strongest antioxidant activity via ABTS (IC50 = 3.26 μg/mL), while antioxidant activity showed no significant differences. A strong correlation (R = 0.81) between TPC and TFC in ASE extracts indicated that flavonoids are major contributors. This study addresses a research gap by systematically comparing UAE and ASE for extracting key bioactives from Cinnamomum zeylanicum in optimising its bioactive recovery for application in functional foods.
Keywords: Ultrasonic-assisted extraction; Accelerated solvent extraction; Antioxidants; Phenols; Cinnamaldehyde